Adhesion of Volcanic Ash Particles under Controlled Conditions and Implications for Their Deposition in Gas Turbines1 . Issue 5 (16th October 2015) - Taltavull, Catalina; Dean, James; Clyne, Trevor William
Abstract : A particular (representative) type of ash has been used in this study, having a particle size range of ∼10–70 μm. Experimental particle adhesion rate data are considered in conjunction with CFD modeling of particle velocities and temperatures. This ash becomes soft above ∼700 °C and it has been confirmed that a sharp increase is observed in the likelihood of adhesion as particle temperatures move into this range. Particle size is important and those in the approximate range 10–30 μm are most likely to adhere. This corresponds fairly closely with the size range that is most likely to enter a combustion chamber and turbine. Abstract : Experimental measurement of ash particle adhesion rates is combined with numerical modeling to establish their velocities and temperatures. Particles of ≈10–30 µm diameter are both large enough to strike solid surfaces and small enough to exceed T g (and hence soften sufficiently to be likely to adhere).